Harmonising Legal and Sharia Principles in Foreign Investment: The Regulatory Framework of Subsidiaries in Saudi Arabia - Alharthi, Saud H.; Alotaibi, Hajed A. (Faculty of Law, University of Muhammadiyah Malang, 2026)
This paper examines how Saudi Arabia’s updated investment regime (2024-2025) and Sharia principles jointly shape the legal and economic environment for establishing subsidiaries. Using a mixed-methods research design, the study combines doctrinal analysis of primary legal sources: the investment laws of 2024 and the implementing regulations of 2025 the 2022 Companies Law. We also considered relevant macroeconomic determinants that inform the foreign direct investments and empirical assessments that adopted the time series data for the period 1960 to 2023. As a finding, this research found that the new Investment Law guarantees equal treatment for domestic and foreign investors and shifts most activities from a licensing model to a streamlined, registration-based entry system, while maintaining approval requirements for sensitive sectors. The 2022 Companies Law enhances structural flexibility by permitting single-member LLCs, modernising governance rules, and removing earlier constraints on shareholder numbers. These changes collectively support holding-company and subsidiary formation.